Cocaine sale restriction (petition) (1916)
1916 1916 1910s 2 pages PETITION. To the Right Hon. HERBERT SAMUEL, M.P., H.M. Chief Secretary of State for the Home Department. Sir, We, the undersigned representatives gathered at the Trades Union Congress held in Birmingham on September 4th, 1916, recognise and support your action in abolishing the free possession and use of Cocaine, with a view to preventing the drug habit amongst those engaged in the War organization. But we are concerned with the fact that, unless UNREGISTERED DENTAL PRACTITIONERS are included amongst such persons whom it is intended shall continue the free use of Cocaine for the legitimate purpose of painless dental operations, a real hardship will be perpetrated upon the WAGE EARNERS, who mainly depend upon the UNREGISTERED PRACTITIONER for dental treatment. We therefore submit that with proper protection (i.e., either by absolute control at the source of supply, or by the issue of licenses by the Clerks to local authorities) permission shall be given to all bona fide UNREGISTERED PRACTITIONERS of dentistry to continue the use of Cocaine. NAME. ADDRESS. SOCIETY. 292C/11.1/1/2/10